Budburst dynamics and tree architecture of deciduous fruit trees - Cook, Nigel C.(Nigel Colin) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph.D. Agric.) -- University of Stellenbosch, 1998.